A high prevalence of chronic gastrointestinal symptoms in adults with cystic fibrosis is detected using tools already validated in other GI disorders. Issue 7 (August 2019) - Hayee, Bu'Hussain; Watson, Kerry-Lee; Campbell, Sanchika; Simpson, Anna; Farrell, Emma; Hutchings, Penelope; Macedo, Patricia; Perrin, Felicity; Whelan, Kevin; Elston, Caroline
Background: People with cystic fibrosis (CF) report a variety of gastrointestinal (GI) symptoms, independent of pancreatic enzyme insufficiency (PEI), reminiscent of other chronic GI disorders. There are currently no accepted or validated assessment tools and neither the range, frequency nor severity of GI symptoms has been systematically described in CF. We present results of a cross-sectional study using established tools and compare them to current measures of quality of life (QOL). Methods: Consecutive patients attending specialist CF appointments were asked to complete questionnaires including the GI Symptom Rating Scale (GSRS); Irritable Bowel Syndrome Symptom Severity Score (IBS-SSS) and Cystic Fibrosis Questionnaire (CFQ-R). Questionnaire terminology was altered to replace references to 'IBS' with 'GI symptoms'. Results: In total, 107 patients were recruited (mean age, 27.8 ± 9.6 years; 60 female), and 94 (88%) had PEI. Body mass index was 22.1 ± 3.6 kg/m 2, forced expiratory volume in one second was 59 + 27.7% predicted. Fifty-three (49.5%) were p.Phe508del homozygous. Overall 69/107 (65%) reported significant GI symptoms independent of PEI or adherence to pancreatic enzyme replacement therapy (PERT), with the four most frequent being attributable to the lower GI tract: bloating/distension, flatulence, abdominal pain and borborygmi (gurgling). There was no numerical correlation between any CFQ-R domain (particularly Digestion domain) and GSRS or SSS. Conclusion: This is the first systematic study measuring GI symptoms in CF using validated GI tools. Symptoms are not related to PERT or genotype and appear to be captured well by the GSRS. Further research will study longitudinal changes with treatment, and therapeutic trials in CF may use these tools to demonstrate a positive impact on 'non-respiratory' symptoms and QOL.